Implementation of Digital Marketing Strategy in Increasing Company Competitiveness - Sugito (Ilomata International Journal of Management, 2024)
In the current technological era, there are many impacts and innovations that can provide more effective solutions in various fields. Especially with digital marketing as an alternative solution. Nowadays, digital marketing can be a way to overcome problems such as lack of funds and promotional limitations that are often faced by business actors, including companies both small and large scale. This alternative solution is found with the current existence of social media such as Twitter, Instagram, Websites and Facebook to create brand awareness, loyalty, sales and engagement. This research is to determine the use of marketing strategies of several businesses that have gone online and their implications for the competitive advantage of these businesses. The method used in this research uses quantitative methods with causality analysis with a population of more than 21,000,000 consumers using non-probability sampling techniques with a total of 100 respondents. The coefficient of determination was calculated at 78 percent. This shows that social media and digital marketing strategies have an influence of 78 percent on competitive advantage. The remaining 22 percent is explained by characteristics not examined in this study, such as capital, resource supply, and management professionalism. This research has discussed the potential of social media as a promotional tool which can be a solution for companies or business people in marketing their products. The potential for social media is quite large from the various promotional methods offered by utilizing social media. Apart from that, looking at the advantages such as budget and wide reach, this is the right solution to overcome the lack of budget and low promotional space currently experienced by business people.